Vertical force distribution between lower limbs in different lunge techniques - Marchetti, Paulo; Martinez, Vincent; Jalilvand, Farzad; Awakimian, Shahan; Lhanie, Leran; Pikkel, Marisa; Nardi Marchetti, Priscyla; Magalhaes, Roberto; da Silva, Josinaldo; Gomes, Willy (British Journal of Healthcare and Medical Research, 2020)
The lunge exercise is considered a bilateral and multi-joint exercise; in this way, each lower limb presents different force distributions in different techniques and body positions. The purpose of this study was to measure the vertical force distribution between lower limbs in different lunge exercises. Thirty-two young, resistance-trained (male=27, 27±6 years, 174.6±9.6 cm, 79.1±14.2 kg; female=7, 24±4 years, 165.2±2.6 cm, 67.1±13.5 kg) performed 3 different lunge techniques on the floor [traditional (TL), partial (PL), and long (LL)] and two on the step [Rear-Foot-Elevated Lunge (RFEL) and RFEL at 50% (RFEL50)] in two static positions (upper and lower) in a randomized, counterbalanced fashion. For the assessment of the vertical force, two portable force plates were positioned under the anterior and posterior lower limb for all lunge techniques. Factorial ANOVA was used to test differences between exercises (TL, PL, LL, RFEL, and RFEL50), limbs and moments. An alpha of 5% was used. In conclusion, lunge techniques as the TL, PL, and LL presented differences in force between legs and positions, however similarities between techniques, and might be applied for different sports under unilateral conditions. Lunges with step (RFEL or RFEL50) presented high asymmetry between lower limbs and emphasis on the anterior leg.